1995
DOI: 10.1074/jbc.270.18.10461
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Mouse Estradiol 17β-Dehydrogenase (A-Specific), a Member of the Aldoketoreductase Family

Abstract: Several mammalian livers contain monomeric 17 beta-hydroxysteroid dehydrogenase (17 beta-HSD) with A-stereospecificity in hydrogen transfer, which differs from the B-specific dimeric enzyme of human placenta in its ability to catalyze the oxidoreduction of xenobiotic trans-dihydrodiols of aromatic hydrocarbons and carbonyl compounds. Here, we report the isolation and characterization of a mouse cDNA clone encoding monomeric 17 beta-HSD of the liver. This clone had an entire coding region for a protein of 323 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 44 publications
1
73
0
Order By: Relevance
“…Type IV 17-HSD is similar to the type II isoform in that it is NAD + -dependent and is principally involved in the oxidation and therefore inactivation of oestrogens and androgens (Adamski et al, 1992). 17-HSD type V belongs to the aldoketoreductase family (Jornvall et al, 1995) while the sixth isoform is a member of the short-chain alcohol reductase family (Deyashiki et al, 1995). A seventh murine isoform of 17-HSD, present in corpus luteum and which possesses reductive activity has recently been described (Nokelainen et al, 1998).…”
mentioning
confidence: 99%
“…Type IV 17-HSD is similar to the type II isoform in that it is NAD + -dependent and is principally involved in the oxidation and therefore inactivation of oestrogens and androgens (Adamski et al, 1992). 17-HSD type V belongs to the aldoketoreductase family (Jornvall et al, 1995) while the sixth isoform is a member of the short-chain alcohol reductase family (Deyashiki et al, 1995). A seventh murine isoform of 17-HSD, present in corpus luteum and which possesses reductive activity has recently been described (Nokelainen et al, 1998).…”
mentioning
confidence: 99%
“…The 17β-hydroxysteroid dehydrogenases are a group of enzymes that are involved in the interconversion of active and inactive forms of androgens and estrogens in the human liver (Deyashiki et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…DNA sequencing confirmed that no unintended base substitution had been incorporated in the coding regions of the expression plasmids. Transformation of the plasmid into E. coli JM109, expression of the recombinant protein and preparation of E. coli cell extract were performed as described [9]. The recombinant enzyme was purified from the cell extract by the method described for the enzyme of Japanese monkey kidney [12].…”
Section: Expression Of Recombinant Dimeric Ddmentioning
confidence: 99%
“…The enzyme exists in multiple forms in mammalian tissues. Most of the enzymes purified from various mammalian tissues are monomeric and have been shown to be identical with 3α-, 17β-and 20α-hydroxysteroid dehydrogenases, aldehyde reductase and\or aldose reductase [5][6][7][8][9][10], which are members of the aldo-keto reductase superfamily [11]. In addition to the monomeric enzymes, dimeric DDs composed of 39 kDa subunits have been isolated from rabbit lens [10], monkey kidney [12,13], pig tissues [14] and dog liver [15].…”
Section: Introductionmentioning
confidence: 99%